Amphiregulin contributes to airway remodeling in chronic allograft dysfunction after lung transplantation. Issue 3 (1st December 2019) - Todd, Jamie L.; Kelly, Fran L.; Nagler, Andrew; Banner, Kane; Pavlisko, Elizabeth N.; Belperio, John A.; Brass, David; Weigt, S. Sam; Palmer, Scott M.
Abstract : Chronic lung allograft dysfunction (CLAD), a condition of excess matrix deposition and airways fibrosis, limits survival after lung transplantation. Amphiregulin (Areg) is an epidermal growth factor receptor (EGFR) ligand suggested to regulate airway injury and repair. We sought to determine whether Areg expression increases in CLAD, localize the cellular source of Areg induction in CLAD, and assess its effects on airway matrix deposition. Lung fluid Areg protein was quantified in patients with or without CLAD. In situ hybridization was performed to localize Areg and EGFR transcript in CLAD and normal lung tissue. Expression of hyaluronan, a matrix constituent that accumulates in CLAD, was measured in Areg‐exposed bronchial epithelial cells in the presence or absence of an EGFR inhibitor. We demonstrated that lung fluid Areg protein was significantly increased in CLAD in a discovery and replication cohort. Areg and EGFR transcripts were abundantly expressed within CLAD tissue, localized to basally distributed airway epithelial cells overlying fibrotic regions. Areg‐exposed bronchial epithelial cells increased hyaluronan and hyaluronan synthase expression in an EGFR‐dependent manner. Collectively, these novel observations suggest that Areg contributes to airway remodeling and CLAD. Moreover these data implicate a role for EGFR signaling in CLAD pathogenesis, suggesting novel therapeutic targets. Abstract : Amphiregulin protein and transcript are increased in lung transplant recipients with chronic allograft dysfunction and bronchial epithelial cells exposed to amphiregulin increase extracellular matrix production in an epidermal growth factor receptor–dependent manner. See the editorial from Zaiss on page 631 .